2011
DOI: 10.1177/1099800410382291
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb Muscle Atrophy Occurs From Peripheral Nerve Damage in a Rat Neuropathic Pain Model

Abstract: Hindlimb muscle atrophy occurs in both ipsilateral and contralateral sides following induction of neuropathic pain by unilateral peripheral nerve damage. Muscle changes of the ipsilateral side are more pronounced than those of the contralateral side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
3
7
1
Order By: Relevance
“…The rate and amount of weight the rats gained aligns with weight gain expectations provided by the breeder (Charles River). Our results contradict those of Choe et al (2011), who found that body weight in rats with neuropathic pain was less than that of control and sham groups over 14 days, including baseline. However, the spinal nerve ligation (SNL) model that Choe et al used to induce neuropathic pain is more invasive than the CCI model we used, which may explain this difference between studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The rate and amount of weight the rats gained aligns with weight gain expectations provided by the breeder (Charles River). Our results contradict those of Choe et al (2011), who found that body weight in rats with neuropathic pain was less than that of control and sham groups over 14 days, including baseline. However, the spinal nerve ligation (SNL) model that Choe et al used to induce neuropathic pain is more invasive than the CCI model we used, which may explain this difference between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…We also observed limping, guarding, and altered gait in these CCI rats, which likely reflected changes in overall animal activity/movement (Bennett & Xie, 1988; Jaggi et al, 2009). Our findings support those of Choe et al (2011), who found that rats with neuropathic pain had lower activity levels than controls, but contradict those of Bennett and Xie (1988), who found no decrease in general activity in the rats with neuropathic pain. The latter authors, however, described activity changes but did not quantify spontaneous activity, as we did.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations